NF-κB Inducing Kinase Regulates Intestinal Immunity and Homeostasis - Wang, Bingran; Shen, Jun (Frontiers in Immunology, 2022)
Intestinal immunity and homeostasis are maintained through the regulation of cytokine trafficking, microbiota, necrosis and apoptosis. Intestinal immunity and homeostasis participate in host defenses and inflammatory responses locally or systemically through the gut-organ axis. NF-κB functions as a crucial transcription factor mediating the expression of proteins related to the immune responses. The activation of NF-κB involves two major pathways: canonical and non-canonical. The canonical pathway has been extensively studied and reviewed. Here, we present the current knowledge of NIK, a pivotal mediator of the non-canonical NF-κB pathway and its role in intestinal immunity and homeostasis. This review also discusses the novel role of NIK signaling in the pathogenesis and treatment of inflammatory bowel disease.